The EU Legal Framework on Irregular Migration – Critique and the Role of the Republic of Serbia - Novaković, Marko (NBP. Nauka, bezbednosti, policija, 2025)
The Common European Asylum System (CEAS) stands as a critical component in managing the escalating challenges posed by irregular migrants in the European Union. This comprehensive review explores the core objectives and strengths of the CEAS, highlighting its pivotal role in harmonizing asylum procedures, upholding human rights, and fostering solidarity among EU member states. The CEAS's accomplishments in reducing disparities and minimizing "asylum shopping" through harmonization are examined, along with its efforts to streamline application processing for greater efficiency. Despite its strengths, the CEAS faces persistent challenges, both internally and externally. Disparities among member states' implementations have led to concerns about unequal treatment, emphasizing the importance of burden-sharing mechanisms such as the Dublin Regulation. The paper underscores that political divisions among EU member states have strained relations, hindering progress toward a more unified approach in managing asylum seekers. The CEAS has also grappled with backlogs and processing delays, which can negatively impact the mental and physical well-being of applicants. External factors, such as the rise of anti-immigrant sentiments and populist movements in certain member states, on the development and implementation of a unified asylum policy. The Republic of Serbia, situated as a vital transit country along the Western Balkan migration route, has faced significant challenges in managing irregular migration flows. Stranded refugees, predominantly in search of asylum in Western and Northern European countries, traverse Serbia, despite it being a temporary stopover rather than a permanent destination. In the wake of an unprecedented influx of migrants in 2015 and early 2016, Serbia adopted a proactive approach, focusing on human rights protection and humanitarian assistance. This response, despite being an internal challenge, proved successful and underscored Serbia's capacity to manage migration crises. The European Union's funding for humanitarian programs and governmental capacity further facilitated Serbia's role in addressing the refugee issue. Serbia's institutional framework for migration management aligns with EU enlargement policies, and the nation has positioned itself as "refugee friendly" in preparation for EU accession. To ensure future preparedness for similar situations, Serbia must invest in institutional memory, recording experiences and solutions for easy future application. Education should be a three-pronged approach, providing institutions, citizens, and immigrants with relevant knowledge and skills. This proactive strategy will help Serbia effectively address irregular migration in the future and promote the rights, safety, and integration of migrants.
Keywords: EU; Irregular migration; CEAS; asylum; Dublin Regulation; Serbia